2019
DOI: 10.1016/j.conctc.2019.100320
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility and acceptability of morning versus evening exercise for overweight and obese adults: A randomized controlled trial

Abstract: BackgroundThe time of day that people exercise could have an influence on the efficacy of exercise for weight loss, via differences in adherence and/or physiological adaptations. However, there is currently no evidence to support an optimal time of day for exercise to maximise efficacy.PurposeTo examine the feasibility and acceptability of prescribed morning and evening exercise.MethodsTwenty inactive, overweight adults aged 18–60 years were recruited for a 12-week intervention and randomized to one of three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 61 publications
5
33
0
Order By: Relevance
“…The characteristics of the 24 included RCTs 10 , 11 , 14 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 with 1802 participants are presented in Table S3 . The meta‐analysis had 41 study arms with 995 individuals in the experimental groups and 447 in the control groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the 24 included RCTs 10 , 11 , 14 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 with 1802 participants are presented in Table S3 . The meta‐analysis had 41 study arms with 995 individuals in the experimental groups and 447 in the control groups.…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneity remained high in the studies with a duration >12 weeks (13 weeks to 16 months), which may be suggestive for problems with adherence with longer intervention durations. Quality assessment of the studies included in the meta‐analysis showed that 15 of the studies had fair or good quality, 10 , 14 , 21 , 22 , 23 , 24 , 27 , 29 , 31 , 32 , 35 , 37 , 39 , 40 , 41 whereas nine were of poor quality 11 , 25 , 26 , 28 , 30 , 33 , 34 , 36 , 38 (Table S2 ). Removing the poor‐quality studies from the meta‐analysis slightly reduced the MD in VO 2max change to 3.89 ml/min/kg (95% CI 2.79, 5.00), P < 0.00001, I 2 = 65% ( N = 999).…”
Section: Resultsmentioning
confidence: 99%
“…Due to a paucity of direct head-to-head comparisons of different exercise times of day, it remains difficult to discern whether there is an optimal time of day for exercise to maximize weight loss benefits. The evidence to date, summarized below, is from observational studies, small randomized trials, and retrospective analyses [42][43][44][45][46][47][48][49][50]. Results from observational studies suggest that there may be an effect of time of day of PA on body weight and BMI.…”
Section: Effect Of Exercise Timing On Body Weight and Body Compositionmentioning
confidence: 99%
“…There is accumulating evidence from observational and clinical studies that the timing of exercise and PA affects body weight regulation [42][43][44][45][46][47][48][49]. Some evidence suggests that morning exercise and PA is associated with more favorable changes in weight and body composition [42,45] and increased ability to prevent weight regain [46,47,49].…”
Section: Effect Of Exercise Timing On Body Weight and Body Compositionmentioning
confidence: 99%
“…During the whole study time, a statistician who will analyse data will be blinded after assignment of participants to the intervention by removing all identi ers. Recruitment rate (the number of individuals recruited out of those interested), consent rate (percentage of individuals who consented to be involved in the study out of those deemed to be eligible), retention rate (proportion of participants who remained in the study during its entirety), lost to follow-up (participants who withdrew, lost to follow-up or who did not attend a follow-up visit) and adherence (total number of visits attended out of the total number of visits)" [20].…”
Section: Assessment Of the Interventionmentioning
confidence: 99%